2008
DOI: 10.1096/fj.08-109462
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin administration after myocardial infarction in mice attenuates ischemic cardiomyopathy associated with enhanced homing of bone marrow‐derived progenitor cells via the CXCR‐4/SDF‐1 axis

Abstract: Mobilization of bone marrow-derived stem cells (BMCs) was shown to have protective effects after myocardial infarction (MI). However, the classical mobilizing agent, granulocyte-colony stimulating factor (G-CSF) relapsed after revealing an impaired homing capacity. In the search for superior cytokines, erythropoietin (EPO) appears to be a promising agent. Therefore, we analyzed in a murine model of surgically induced MI the influence of EPO treatment on survival and functional parameters as well as BMC mobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 47 publications
8
60
0
3
Order By: Relevance
“…The use of EPO is of therapeutic interest for ischemic injury as it is associated with tissue protective effects through activation of EPO receptorrelated antiapoptotic pathways, for example, PI3K/Akt 51 as well as neovascularization of the ischemic tissue. 52 This neovascularization occurs primarily via the CXCR4/SDF-1 axis, which is the key cellular anchor within the BM microenvironment and a pivotal element of EPC mobilization and homing. 52,53 Interestingly, the WT and SK-1-KO groups showed no difference in either the number of Lin Ϫ /ckit ϩ /flk-1 ϩ cells in the BM or their capabilities to migrate toward VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The use of EPO is of therapeutic interest for ischemic injury as it is associated with tissue protective effects through activation of EPO receptorrelated antiapoptotic pathways, for example, PI3K/Akt 51 as well as neovascularization of the ischemic tissue. 52 This neovascularization occurs primarily via the CXCR4/SDF-1 axis, which is the key cellular anchor within the BM microenvironment and a pivotal element of EPC mobilization and homing. 52,53 Interestingly, the WT and SK-1-KO groups showed no difference in either the number of Lin Ϫ /ckit ϩ /flk-1 ϩ cells in the BM or their capabilities to migrate toward VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…There are several models in both small [114][115][116][117] and large animals [118][119][120][121] in which a major coronary artery or multiple branches are occluded for the specific purpose of inducing significant myocardial ischemia and infarction for the subsequent analysis of neovasculogenesis and arteriogenesis in response to experimental therapies (Table 4). These models can entail permanent occlusion or a prolonged occlusion followed by reperfusion.…”
Section: Acute Coronary Occlusion Modelsmentioning
confidence: 99%
“…76 Finally, the hematopoietic cytokine erythropoietin, currently being tested in several clinical trials, was shown to mobilize EPCs 77 and to stimulate the recruitment and survival of bone marrow-derived progenitor cells to the heart. 78 Kinases Downstream of the growth factors, antiapoptotic kinases might be additional attractive targets for improving progenitor cell function. Overexpression of Akt, glycogen synthase kinase, and integrin-linked kinase increased the function of delivered cells, probably also as a result of increased survival.…”
Section: Targeting Adhesion Molecules: Integrins and Selectinsmentioning
confidence: 99%